Ratio Decidendi Hakim dalam Penetapan Nafkah Iddah terhadap Istri yang Nusyuz Perspektif Dhariah - Siti Hajrah; Saifullah Saifullah; Abid Rohmanu (Journal of Economics, Law, and Humanities, 2025)
This study is motivated by legal issues regarding the provision of iddah maintenance for a wife who is considered nusyuz in divorce cases at the Religious Court of Ponorogo. This study aims to analyze the judges’ ratio decidendi in determining iddah maintenance for a nusyuz wife and to examine its relevance to the theory of dhariah in Islamic law. The qualitative research employs a normative juridical method using a statutory and case law approach. Data were obtained through interviews with judges handling similar cases and documentation such as court decisions and relevant Supreme Court Circular Letters (SEMA). The data were analyzed descriptively and analytically by exploring the judges’ legal and moral considerations in making decisions. The results show that the judges’ ratio decidendi in granting iddah maintenance is based on the absence of clear evidence of nusyuz, thereby affirming the wife’s right to maintenance based on principles of justice and protection of women. Conversely, when nusyuz is proven, judges may deny iddah maintenance by applying sadd al-dhariah to prevent social harm. The relevance of dhariah theory in these decisions emphasizes the importance of balancing public benefit (maslahah) and substantive justice. Thus, judges’ decisions toward maslahah can be essential to strengthen gender justice in Islamic family law.